Do coaching style and game circumstances predict athletes' perceived justice of their coach? A longitudinal study in elite handball and volleyball teams - de Backer, M.; Reynders, B.; Boen, F.; Van Puyenbroeck, S.; Vande Broek, G. (PLOS ONE, 2018)
The present longitudinal study is the first to examine game to game fluctuations of perceived justice of elite volleyball and handball coaches. More specifically, we studied whether coaching style (i.e., need support versus control), coach behaviors (decision justifications), player`s status (i.e., starter or substitute), and game result (win/loss) predicted athletes` perceived justice and its fluctuations. Methods: A longitudinal questionnaire study was performed during 6 consecutive weeks among Belgian female volleyball (N = 57) and male handball players (N = 39). We administered a general questionnaire (i.e., need support/control) the first week, and game-specific questionnaires (i.e., justice, decision justifications, game circumstances) after six consecutive games. Because game-to-game measures (i.e., within-athlete) were nested into individuals (between-athletes) we conducted Hierarchical Linear Modeling to examine the hypotheses. Results: Multilevel analyses showed that 49% of the variance of perceived justice was situated at the within-athlete level. Furthermore, coaches` need support and the provision of decision justifications were positive predictors of athletes` perceived justice of the coach. More specific, the impact of justifications was less strong in a high need supportive environment and stronger in a high controlling environment. Finally, both the status of the player and the game result were negative predictors of athletes` perceived justice. Conclusions: We can conclude that athletes` perceived justice of their coach shifts considerably from game-to-game. Furthermore, the coaching style and coaching behaviors can help to overcome the negative effects of specific game circumstances such as being a substitute or losing a game on athletes` perceived justice of the coach.